﻿Development and validation of an RP-HPLC method for analysis of 2-(5-(4-chlorophenyl)-3-(ethoxycarbonyl)-2-methyl-1H-pyrrol-1-yl)propanoic acid and its impurities under different pH - Vania Maslarska; Stanislav Bozhanov; Stanislava Vladimirova; Lily Peikova; Diana Tzankova; Maya Georgieva (Pensoft Publishers, 2022)
A simple, fast and selective stability indicating RP-HPLC method was applied for following the degradation and appearance of impurities of previously synthesized 2-(5-(4-chlorophenyl)-3-(ethoxycarbonyl)-2-methyl-1H-pyrrol-1-yl)propanoic acid. The chromatographic separation was achieved on a C18 column (150×4 mm i.d., 5 μm) using a mobile phase consisting of Acetonitrile: Phosphate buffer, pH=3, (50:50% v/v) with isocratic elution at a flow rate of 1.0 mL min−1 and temperature of the column of 30 °C applying a UV/VIS detector at 225 nm. The method was validated according to the ICH guidelines. A process related impurity was determined at pH 9.0 corresponding to ethyl 2-acetyl-4-(4-chlorophenyl)-4-oxobutanoate. No change in the structure was detected at pH = 7.4.